To evaluate the expression \( \frac{2}{3}(6x + 12) + 5x \) at \( x = 3 \):
-
Substitute \( x = 3 \) into the expression: \[ \frac{2}{3}(6(3) + 12) + 5(3) \]
-
Calculate \( 6(3) + 12 \): \[ 6(3) = 18 \] \[ 18 + 12 = 30 \]
-
Substitute this back into the expression: \[ \frac{2}{3}(30) + 5(3) \]
-
Calculate \( \frac{2}{3}(30) \): \[ \frac{2}{3} \times 30 = 20 \]
-
Calculate \( 5(3) \): \[ 5(3) = 15 \]
-
Now combine the results: \[ 20 + 15 = 35 \]
Thus, the value of the expression when \( x = 3 \) is \(\boxed{35}\).